Interrelationship between facial pattern, malocclusion, TMDs, head and neck posture and type of breathing in young people - Valinhas, S (2018)
Objectives: To compare occlusal, facial, and craniocervical postural characteristics according to the breathing pattern, study the association between temporomandibular disorders’ (TMDs) class and severity, gauge the influence of the breathing pattern, head and neck posture, occlusal class, and facial pattern on TMDs severity and the lower cervicofacial ratio, and identify any prevalent differences in TMDs severity by gender. Methods: This cross-sectional study included a convenience sample of 139 individuals, 81 females (58.3%) and 58 males (41.7%), with a mean age of 13.0±0.72 years old. Data were collected from observations, medical forms and photographic records. We classified TMDs severity according to Fonseca Anamnestic Index and used Software for Postural Assessment. Results: Compared to nasal breathers, oral breathers exhibited a predominance of Class II occlusion (p<0.01), a convex profile (p<0.05), increased cervicofacial ratio (p<0.01), and a tendency for head anteriorization (p<0.05). An association between TMDs and individuals with Class II occlusion was also found (p<0.01). Oral breathers showed a greater risk of increased lower cervicofacial ratio and mild TMDs (OR: 9.64 and 4.01, respectively). Signs and symptoms of TMDs appeared in 60% of young females, though the difference between genders was not significant (p=0.290). Conclusions: We detected associations between oral breathing and head anteriorization, TMDs, Class II malocclusion, convex facial profile, and increased lower cervicofacial ratio. TMDs were associated with occlusal Class II, and oral breathing increased the risk of developing mild TMDs and increased lower cervicofacial ratio.